Importance of Current Ratio and Dividend Yield Ratio in Moderating Process on Stock Prices - Deni Sunaryo (Yayasan Ilomata, 2022)
This study aims to determine the influence of Gross Profit Margin, Receivable Turn Over and Long Term Debt to Equity Ratio on Stock Price with Current Ratio and Dividen Yield Ratio as moderating variables. This study used the object of the Batubara subsector company on the Southeast Asian Stock Exchange for the period 2012-2020. The data collected is secondary data with documentation methods in the form of company annual reports. The analysis tool used to test hypotheses is the IBM SPPS V26. The sampling method used in this study using purposive sampling techniques was obtained by 9 companies that presented complete financial statements, so that 81 samples were obtained. The analytical techniques used are deskriptif statistical analysis, classical assumption test, moderated regression analysis (MRA), multiple linear regression, t test test, and f test. The results of the study partially concluded that Gross Profit Margin has no significant effect on Stock Price, Receivable Turn Over has a significant effect on Stock Price and Long Term Debt to Equity Ratio has no significant effect on Stock price. The results of the study simultaneously showed that the value of Fcount 13,962 and Ftable 2,72 means that Fcount > Ftable or a significant value of 0,000<0,05. So far, Gross Profit Margin, Receivable Turn Over and Long Term Debt to Equity Ratio simultaneously have a significant effect on Stock Prices. The results of moderately regression analysis (MRA) research show that Current Ratio does not moderate Gross Profit Margin to Stock Prices, Current Ratio does moderate Receivable Turn Over to Stock Price and Current Ratio does not moderate Long Term Debt to Equity Ratio on Stock Prices, Dividen Yield Ratio does not moderate Gross Profit Margin to Stock Prices, Dividen Yield Ratio does moderate Receivable Turn Over to Stock Price and Dividen Yield Ratio does not moderate Long Term Debt to Equity Ratio on Stock Prices.